Drepanoneura gen. nov. for Epipleoneura letitia and Protoneura peruviensis, with descriptions of eight new Protoneuridae from South America (Odonata: Protoneuridae) - Von Ellenrieder, Natalia; Garrison, Rosser W. (Zootaxa, 2008)
A new genus, Drepanoneura (type species Drepanoneura loutoni sp. nov.), is described to include Epipleoneura letitia Donnelly, Protoneura peruviensis Fraser, and six new congeneric species from South America: D. donnellyi, D. flinti, D. janirae, D. loutoni, D. muzoni, and D. tennesseni. Drepanoneura is similar to Epipleoneura and Epipotoneura in venational characters, but differs from them in morphology of male cercus, genital ligula, female pronotum, and epiproct. A new species of Epipleoneura from Venezuela, E. demarmelsi, and a new species of Epipotoneura from Brazil, E. machadoi, are described, and diagnostic illustrations for the poorly known Epipotoneura nehalennia Williamson are also presented. A generic characterization, diagnoses, and keys for species of Drepanoneura are provided, as well as diagnostic illustrations and distribution maps for all involved species.